Krisis Ekonomi, Kesejahteraan dan Tata Pemerintahan yang Baik : Perspektif Islam - Winata Wira; Yudhanto Satyagraha Adiputra (Kemudi, 2021)
Lessons from recurring economic crises have been of particular concern to the Islamic world. Mostly Islamic countries are of middle and low-income economies that they had been inevitably suffered from extensively negative consequences caused by economic crisis such as drastic decline in welfare. The accumulation of under-performance institution and complexity of the prevailing socio-economic problems have made recovery efforts either harder steps to take or even further distances to approach merely the pre-crisis level. Using analysis based on Islamic perspective, this paper seeks to explore on economic crises, welfare and hope for good governance would be as a fundamental resilience in times of crisis. From the elaboration of literature review which encompasses thoughts of a number of Islamic economic thinkers as well as empirical studies, Islamic countries should take all determination in good governance reform as it is directed by Islamic teaching to safeguard intact welfare of the Islamic notion of which consists of ad-din (religion), al-maal (wealths), al-aql (intellect), an-nafs (life), and an-nasl (posterity).